The importance of Civil Law and codification for society. Interview to Fernando Vidal Ramírez - Pérez Caruajulca, Miguel Ángel (2014)
Civil Law is still one of the most important areas of the legal field. Its consideration as the Common Law is still dormant.In this sense, Professor Fernando Vidal Ramirez talks about the birth, evolution and importance of Civil Law in the society, explaining the role played by civil codification. Finally, he talks about his experience as a member of the Reformer Commission of the 1936 Civil Code, which allowed the provision of the still in force Peruvian Civil Code of 1984.